Evaluation of the Effectiveness of E-Training in Preparing Scientific Work Using the Kirkpatrick Model - Satyawati, Sophia Tri Satyawati; Marinu Waruwu (Jurnal Pendidikan Indonesia, 2024)
Preparing scientific work is a crucial skill, especially for academics, researchers and students. However, not all individuals have access to direct training or have sufficient skills in preparing scientific papers. This research aims to evaluate training programs in developing "best practice" scientific work for teachers and provide recommendations for improving training programs. The method used in this research is evaluation using the Kirkpatrick model which includes evaluating reactions, learning, behavior and results using a mixed method approach, namely the Concurrent Embedded Model. Quantitative data was collected using test, questionnaire and assignment techniques. Qualitative data was collected using interview techniques, observation and document study. Research subjects included teachers, principals, coaches and committee members. Quantitative data was analyzed descriptively by calculating percentages, categorization, and T test. Qualitative data was analyzed using the Miles and Huberman model. The results showed that the reaction stage was at the very satisfied category level; increasing the domains of knowledge, attitudes and skills identified at the learning stage; while the behavior and outcome stages are at the good category level. Organizing e-training can meet the expectations and needs of participants, mable to increase participants' knowledge and skills in writing scientific papers. The implications of the research for educational institutions need to plan ongoing mentoring programs for teachers in writing scientific papers, and schools need to provide opportunities for teachers to participate in various training courses in preparing scientific papers.